Studies on growth and cocoon parameters of Bombyx moriL. exposed to various temperature (International Journal of Food and Nutritional Sciences, 2022)
The mulberry silkworm, or Bombyx mori L., is exceedingly delicate, extremelysensitive to changes in its surroundings, and incapable of surviving in harsh environments. Thesilkworm's morphological and biochemical characteristics, including the diameter and weight ofthe cocoon, the length and weight of the larvae, and the protein content of the silk gland andcocoon, are impacted by seasonal variations.